The Museum Between Evolution and Diversity: The Challenges of the History Museum as a Model - Othman, Naima (Journal of the College of Education for Girls for Humanities, 2026)
Evolution of the definition of the museum and its various types; the history museum and the challenges of society in the twenty-first century. The museum is a concept related to human existence that has evolved on constantly throughout history generating several forms and types of museums responding to the new challenges in society Certainly, several definitions and redefinitions of the museum as well as the classifications of the various types and forms, the most remarkable one is that of the museum of history, which has been the subject of several debates, although it is the most widespread form in XXI century society as guardian of history, memory and identity.